Integrated Project Delivery Implementation Challenges in the Construction Industry - Kahvandi, Zahra; Saghatforoush, Ehsan; ZareRavasan, Ahad; Preece, Christopher (Salehan Institute of Higher Education, 2019)
Huge financial resources are spent in the construction industry all over the world, which are frequently wasted largely due to a lack of proper planning. In recent decades, in an attempt to overcome challenges, various contractual and administrative systems have been used by construction owners/clients. One such system has been Integrated Project Delivery (IPD). Its implementation has, however, experienced drawbacks. Identifying such drawbacks is an initial step in attempting to resolve them, and this paper aims to identify and prioritize the IPD implementation drawbacks in the context of the Iranian construction industry. A comprehensive list of IPD implementation drawbacks is prepared using a questionnaire survey. An in-depth literature review of the IPD concept has been combined with a review of various case studies applying the IPD system. The results were analyzed using the Robust Exploratory Factor Analysis (EFA) method. 22 drawbacks in the Construction Industry were categorized under four themes; contractual, environmental, managerial, and technical. Results show that contractual drawbacks are the most significant. The implication of this research is that identifying and classifying IPD implementation drawbacks provides a useful reference to managers and owners of the construction industry, for identifying and codifying solutions to overcome them.